Asociación entre Diabetes Mellitus tipo 2 y Cirrosis Hepática en pacientes adultos - Piscoche Valverde, Yelina Madeleyne (2019)
The prevalence of diabetes mellitus (DM) open in patients with liver cirrhosis of any etiology is around 30%. There are 2 aspects in the relationship of DM and liver cirrhosis: a) hereditary type 2 DM, (which is part of the metabolic syndrome with obesity, hypertriglyceridemia and portal hypertension), can be a risk factor for development of liver disease. At a time when obesity and DM have increased to the level of public health problems, the liver diseases that result from these metabolic alterations become more relevant, and b) on the other hand, DM can be a complication of cirrhosis . This diabetes is known as "hematogenous diabetes" (DH). Both types of DM are associated with an increase in complications and death. The treatment of cirrhotic diabetes is complex due to the liver damage and the hepatotoxicity of some oral hypoglycaemic agents. Currently, there are no studies that evaluate the best therapeutic regimens for diabetes in cirrhotic patients and it is also unknown if the control of DM modifies the natural history of liver disease.